On derivation of equations of dynamics for a certain class of models of mechanical systems - Grabysz, Witold (Computer Assisted Methods in Engineering and Science, 1996)
Mechanical systems are quite often modelled as sets of stiff and flexible elements. If some conditions concerning connections of these elements are fulfilled, then we get a physical model having an interesting feature: it is quite easy to derive equations of motion from a diagram representing in a natural, intuitive manner the structure of the system. The algorithm for such derivation, including creation of a simple graphical user interface is presented in the paper. The algorithm takes advantage of the software package MATLAB /SIMULINK.